2019
DOI: 10.1111/tpj.14570
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MYB4 plays dual roles in flavonoid biosynthesis

Abstract: Flavonoids are major secondary metabolites derived from the plant phenylpropanoid pathway that play important roles in plant development and also have benefits for human health. So-called MBW ternary complexes involving R2R3-MYB and basic helix-loop-helix (bHLH) transcription factors along with WD-repeat proteins have been reported to regulate expression of the biosynthetic genes in the flavonoid pathway. MYB4 and its closest homolog MYB7 have been suggested to function as repressors of phenylpropanoid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(113 citation statements)
references
References 56 publications
(89 reference statements)
2
92
0
Order By: Relevance
“…It was reported that AtMYB75 can interact with AtKNAT7, which functions as a negative regulator of secondary cell wall formation in interfascicular fibers (Bhargava et al, 2010;Wang et al, 2020a). A recent study further demonstrated that AtMYB4, a transcriptional repressor of lignin biosynthesis, along with its homologs MYB7 and MYB32, can attenuate the transcriptional function of MYB75-TT8-TTG1 complexes in flavonoid metabolism by interacting with the TT8 transcription factor (Wang et al, 2020b). The coordinated action of MYB repressors and activators has been proposed as a fine-tuning mechanism for the regulation of plant secondary metabolism (Bomal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that AtMYB75 can interact with AtKNAT7, which functions as a negative regulator of secondary cell wall formation in interfascicular fibers (Bhargava et al, 2010;Wang et al, 2020a). A recent study further demonstrated that AtMYB4, a transcriptional repressor of lignin biosynthesis, along with its homologs MYB7 and MYB32, can attenuate the transcriptional function of MYB75-TT8-TTG1 complexes in flavonoid metabolism by interacting with the TT8 transcription factor (Wang et al, 2020b). The coordinated action of MYB repressors and activators has been proposed as a fine-tuning mechanism for the regulation of plant secondary metabolism (Bomal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was expressed at significantly higher levels in APSP and CPSP than in O271, at all stages. As the negative regulator of anthocyanin and proanthocyanidin biosynthesis (Jin et al, 2000;Wang et al, 2020), MYB4 showed significantly increased expression at the Petal2 stage. One repressor of anthocyanin biosynthesis (MYBL2) and one activator of proanthocyanidin accumulation (WRKY44) were dramatically up-and down-regulated at the early flower developmental stages, respectively (Ishida et al, 2007;Dubos et al, 2008), corresponding to the unaltered expression level of most of the late pathway genes in anthocyanin and proanthocyanidin biosynthesis.…”
Section: Aba Biosynthesis Is Not Disrupted In Orange-flowered Plantsmentioning
confidence: 99%
“…MYB4 in particular regulates abiotic stress responses towards UV-B light and cadmium toxicity in Arabidopsis thaliana [82,83] and cold in Oryza sativa [84]. It has also been shown to influence the biosynthesis of flavonoids [85]. MYB61 participates in the response to cold stress in Medicago truncatula [86].…”
Section: Functional Analysis Of the Candidate Gene And Transcriptionmentioning
confidence: 99%